Infrastructure competitiveness of regencies and cities in Java Island - Andri Kurniawan (Universitas Negeri Malang, 2023)
Regional infrastructure competitiveness is highly influential in regional development. This research aims to: (1) compile the infrastructure competitiveness index for regencies or cities in Java, (2) assess the level of infrastructure competitiveness disparity between regencies or cities, and (3) analyze the relationship between the regional infrastructure competitiveness index and economic growth. In investigating the regional infrastructure competitiveness index, five infrastructure groups were assessed, namely social infrastructure, information technology, transportation, economy, and culture. The infrastructure competitiveness between regions (regencies and cities) was determined by scoring and standardization. The Gibbs & Martins index was used to measure the infrastructure competitiveness gap. Meanwhile, the relationship trend between the infrastructure competitiveness index and regional economic growth was analyzed using crosstabs. For the competitiveness of regional infrastructure in Java, this research observed spatial variations between regencies or cities. Besides, the regional infrastructure competitiveness index is not distributed concentrically and tends to have a diffuse pattern. Different distributions of the competitiveness index were also observed in every group of infrastructure. In general, clusters of high infrastructure competitiveness were observed in each province on the island of Java. The Gibbs & Martins index measurement illustrates Java's high regional infrastructure gap. The gap is due to the infrastructure in development centers and activity centers not being accompanied by infrastructure development in the hinterland areas. The social infrastructure has the highest level of inequality. Besides, this research also found a different relationship between infrastructure competitiveness and economic growth in the provinces.